Model Dinamik Vigor Daya Simpan Benih Kedelai pada Penyimpanan Terbuka - Wahyuni, Ari; Suhartanto, M. R.; Qadir, Abdul (Jurnal Penelitian Pertanian Tanaman Pangan, 2015)
Soybean seed viability declines during seed storage. Soybean seed deteriorates rapidly, affected by its high protein content and often high humidity in the tropical environment. This research was aimed to develop dynamic model of soybean seed viability in an open storage. The study was conducted in three stages, namely: 1) desk study, 2) seed storage experiment, 3) development of seed storage model, simulation and verification of the model. The second stage of the experiment consisted of soybean seed storing and germination testing using completely randomized design. Treatments were three initial moisture content (7-8%, 9-10% and 11-12%) and four varieties of soybean (Anjasmoro, Wilis, Detam-1 and Detam-2). The results showed that the seed behaviour during storage period were affected by initial seed moisture content, initial viability, varieties and environmental condition. Therefore, seed moisture content, initial viability and varieties may be used as input model. Moisture content, integreting seed respiration, electric conductivity and seed storability vigor (VDSDB) were as model output. Simulation of Seed Storability Vigor Prediction Model with Model Construction Layer-Stella (MCLS) using relative humidity (RH), temperature, seed permeability, initial moisture content and initial viability as input model could logically predict the seed moisture content and seed storability vigor (VDSDB).